Perbedaan Pengetahuan dan Sikap Ibu Sebelum dan Sesudah Penyuluhan Dengan Menggunakan Media Leafleat Tentang Pemantauan Status Gizi Balita di Wilayah Kerja Puskesmas Kemiling - Fatmasari, Yeni; Riyanti, Riyanti; Sari, Fitri Eka; Samino, Samino (Jurnal Ilmiah Manusia Dan Kesehatan, 2026)
Bandar Lampung ranks fourth in the prevalence of stunting (44.6) in Lampung province after Central Lampung (52.7%), Pesawaran (50.8%), Metro (47.3%). According to the 2014 Nutritional Status Assessment data, the highest prevalence of stunting in toddlers in the Bandar Lampung area is in Rajabasa District (55.6%), the second highest is in Kemiling District (39.6%). The nutritional status of malnutrition in the Kemiling Health Center has increased every year from 1.8% in 2020 to 2.4% in 2021. The aim was to determine the differences in knowledge and attitudes of mothers before and after counseling using leaflet media on monitoring the nutritional status of toddlers in the Kemiling Health Center Work Area. This study is a quantitative study using an experimental method with a population of 1150 mothers of toddlers and a sample of 98 respondents. The sampling technique used was Purposive Sampling. Data were tested univariately and bivariately using the Paired Sample T-Test. The results of the study showed that the nutritional status of toddlers at the Kemiling Health Center was mostly normal nutritional status of 68 toddlers (69.4%), overnutrition of 22 toddlers (22.4%) and undernutrition of 8 toddlers (8.2%). The average value of knowledge of toddler mothers increased before counseling using leaflet media, namely 7.78 (64.8%) and after counseling using leaflet media to 9.22 (76.8%). The average value of attitudes of toddler mothers increased before counseling using leaflet media, namely 41.22 (68.7%) and after counseling using leaflet media to 50.49 (84.1%). There was a difference in knowledge (p-value 0.000) and attitudes (p-value 0.000) of toddler mothers before and after the distribution of leaflets related to monitoring toddler nutrition at the Kemiling Health Center, Bandar Lampung. Keywords : Nutritional Status, Leaflet, Toddlers, Monitoring